POME Processing with Bioremediation Using Indigenous Bacteria (Bacillus toyonensis and Stenotrophomonas rhizophila), Electrocoagulation, and Bioremediation assisted with Electrocoagulation Methods - Bambang Yudono; Sari Ulfariani; Fatma Fatma; Parwiyanti Parwiyanti; Eka Lidiasari (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
Palm oil mill effluent (POME) is wastewater containing dissolved materials with concentrations above the threshold. Generally, POME processing in Indonesia uses an open pond system. It is less efficient because it requires large areas and causing greenhouse gas effects. This research aims to improve the POME processing, three methods were studied; bioremediation using enrich indigent lypholitics bacteria (Bacillus toyonensis and Stenotrophomonas rhizophila.), electrocoagulation system, and combination of those methods. The parameters were measured were oil and fat contents, COD, pH, TSS, TDS, Fe and Cu metals. In the electrocoagulation method, the electrodes were used iron electrodes with a variation of electrical voltage 1.5, 3, 4.5 and 6 V. The bioremediation using indigent bacteria results in the removal of oil and fat -74.62%, COD -52.44%, TSS -43.11% and pH 6.38 at the incubation time for 6 days, TDS 21.42%, Fe -5.3% and Cu -64.70%. The electrocoagulation methods results oil and fat removal were -93.27%, COD was -85.71%, TDS -39%, TSS -84%, Cu -46%, Fe +92.35%, and pH 11.39 at a voltage of 6 V for 6 h. The combination of the two methods can reduce oil and fat levels by -87.39%, COD -56.70%, TDS -0.42%, TSS +15.88%, Cu -23.33%, Fe +93.74% and pH 8.82. The three methods were studied can improve the POME processing significantly.